2021
DOI: 10.3389/fmicb.2021.643950
|View full text |Cite
|
Sign up to set email alerts
|

High Diversity and Functional Potential of Undescribed “Acidobacteriota” in Danish Wastewater Treatment Plants

Abstract: Microbial communities in water resource recovery facilities encompass a large diversity of poorly characterized lineages that could have undescribed process-critical functions. Recently, it was shown that taxa belonging to “Acidobacteriota” are abundant in Danish full-scale activated sludge wastewater treatment plants (WWTP), and here we investigated their diversity, distribution, and functional potential. “Acidobacteriota” taxa were identified using a comprehensive full-length 16S rRNA gene reference dataset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Many of these MAGs are from groups known to encode extracellular cytochromes for mediating extracellular electron transfer, such as Anaeromyxobacter (Myxococcota), Geobacterales (Desulfuromonadota) (76) and Geothrix (Acidobacteriota) (77). Multi-heme cytochromes were also previously reported in the same Geothrix -related MAGs (78), although sub-cellular locations were not predicted. Recent experimental work showed increases of Geothrix and Ignavibacteria spp.…”
Section: Resultsmentioning
confidence: 71%
“…Many of these MAGs are from groups known to encode extracellular cytochromes for mediating extracellular electron transfer, such as Anaeromyxobacter (Myxococcota), Geobacterales (Desulfuromonadota) (76) and Geothrix (Acidobacteriota) (77). Multi-heme cytochromes were also previously reported in the same Geothrix -related MAGs (78), although sub-cellular locations were not predicted. Recent experimental work showed increases of Geothrix and Ignavibacteria spp.…”
Section: Resultsmentioning
confidence: 71%
“…Actinobacteriota , as well as Proteobacteria and Bacteroidota , have been reported to be some of the core phyla that are widespread in wastewater treatment systems 18 , 19 . Acidobacteriota are involved in P-removal and have the potential to utilize various organic compounds, including glucose, xylose, acetate, and fatty acids 20 . After Proteobacteria and Bacteroidota , the next most abundant phyla in the activated sludge were Actinobacteriota and Patescibacteria (especially the uncultured Saccharimonadales ).…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterium was also an indicator taxon under saline groundwater irrigation, showing an increase in arabinogalactan-peptidoglycan (cell wall) synthesis that may serve as a potential mechanism for tolerating salinity stress. Subgroup_10 genus (Acidobacteriota) abundance was higher in soil under saline water irrigation, whose members are reported to accumulate starch (Kristensen et al, 2021) and starch accumulation was reported to provide osmoprotectant effect for bacteria against salinity stress (Qiao et al, 2018). The increased Saline groundwater irrigation increased the abundance of Microvirga (Alphaproteobacteria), a free-living, nitrogen-fixing, and nitrate-reducing bacterium isolated from desert soil (Amin et al, 2016), suggesting that it may function as a nitrifier despite salinity-stress.…”
Section: Saline Groundwater Irrigation Impacts Bacterial Composition ...mentioning
confidence: 99%